Environmental news and stock markets performance: Further evidence for Argentina - Mariana Conte Grand; Vanesa V. d' Elia (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
More and more firms tend nowadays to adopt environment-friendly attitudes. Their motivation originates in local environmental regulations or requirements of foreign markets to which firms export (both induced by consumers and investors' valuation of pro-environment initiatives). There is a well-established literature capturing the impact on stock prices of environmental information releases using the event study methodology. Studies are usually based on information environmental regulation (i.e., the regulator announcement of emissions or compliance status with respect to standards) or on simple media coverage of environmental news. Dasgupta, Laplante and Mamingi (2001) is one of the few references to show that public information on environmental behavior has impact on stock prices in the developing world. It includes Argentina in its analysis together with Chile, Mexico and the Philippines. In this manuscript, we focus specifically on Argentina. We find that positive environmental news have no impact, while negative news do have an effect on average rates of return a few days following its appearance. But, when focusing on different types of positive news, we find that ISO certification has no effect whatsoever, while investment decisions do have some positive significant influence on returns. On the other side, negative news influence on stock returns is particularly significant for events linked to citizen complaints and government rulings (confirming other studies results) and for media coverage of oil company issues. However, we find abnormal returns of a much smaller magnitude than other studies for developing countries. We believe that is readonable because there seem to be no reason why the level of abnormal returns (not its volatility) should be larger for environmental news in developing countries than in developed ones.
Keywords: Q58; G14; 330; developing countries; environmental management; environmental news; capital markets; event study; Umweltmanagement; Börsenkurs; Entwicklungsländer